From skepticism to mutual support: towards a structural change in the relations between participatory budgeting and the information and communication technologies? - Allegretti, Giovanni (2012)
Peer-reviewed conference paper originally presented at the workshop Legitimacy 2.0: E-democracy and Public Opinion in the Digital Age, at the IVR World Congress held in Frankfurt, August 18th 2011